2018
DOI: 10.1590/s0102-865020180070000006
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and antioxidant effects of Eremurus spectabilis Bieb. methanol extract and its isolated component isoorientin on indomethacin induced gastric ulcers in rats

Abstract: The gastroprotective effects of E. spectabilis and its major constituent isoorientin in rats for the first time. Detailed analyses suggested that potential antioxidant activity of both plant extract and isoorientin mediates the gastroprotective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
(33 reference statements)
1
8
0
Order By: Relevance
“…In the naproxen-induced gastric ulcer model in rats, pretreatment with 20, 50, and 80 mg/kg anthocyanins twice daily for 3 days reduced gastric MDA levels and increased CAT and SOD activity [ 81 ]. Isoorientin, derived from Eremurus spectabilis , significantly decreased the MDA level ( p < 0.05) and increased SOD activity and the GSH level in gastric tissues at doses of 25, 50, and 100 mg/kg [ 82 ]. Flavonoids, including hesperidin [ 47 , 48 , 54 , 83 ], diosmin [ 63 ], nobiletin [ 64 ], and genistein [ 62 ], aromadendrin-4′- O -methyl-ether and kaempferide [ 84 ] from Brazilian green propolis, and biochanin A [ 85 ] from soy and red clover also showed positive effects in treating peptic ulcer by increasing activities of antioxidant enzymes in vivo.…”
Section: Anti-ulcer Mechanisms Of Flavonoidsmentioning
confidence: 99%
“…In the naproxen-induced gastric ulcer model in rats, pretreatment with 20, 50, and 80 mg/kg anthocyanins twice daily for 3 days reduced gastric MDA levels and increased CAT and SOD activity [ 81 ]. Isoorientin, derived from Eremurus spectabilis , significantly decreased the MDA level ( p < 0.05) and increased SOD activity and the GSH level in gastric tissues at doses of 25, 50, and 100 mg/kg [ 82 ]. Flavonoids, including hesperidin [ 47 , 48 , 54 , 83 ], diosmin [ 63 ], nobiletin [ 64 ], and genistein [ 62 ], aromadendrin-4′- O -methyl-ether and kaempferide [ 84 ] from Brazilian green propolis, and biochanin A [ 85 ] from soy and red clover also showed positive effects in treating peptic ulcer by increasing activities of antioxidant enzymes in vivo.…”
Section: Anti-ulcer Mechanisms Of Flavonoidsmentioning
confidence: 99%
“…Risk assessment for any substance prior to install in any biological system is an important issue In essence, checking of the inflammatory response to a substance and the effects of it on cell membrane stability are two major consequences [23,24]. Plants containing secondary metabolites, especially the polyphenols and flavonoids alkaloids having antioxidant capacity may impart anti-inflammatory effects in biological systems [25,26,27]. Generally, inflammation is a type of protective response, but at severity level, it may cause serious problems in our body, including cardiovascular and neurological diseases and disorders [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…3 Several plants have been reported to be effective in the treatment of peptic ulcer. Some of these plants include Hibiscus asper, 4 Eremurus spectabilis, 5 Cnidoscolus aconitifolius. 6 Serafino et al 7 reported that many plant extracts are as effective as the synthetic drugs with no or insignificant adverse effect.…”
Section: Introductionmentioning
confidence: 99%